Regulation of cancer by inflammasomes: from inflammation to tumorigenesis - Malvankar, Shivani; Jaiswal, Pundrik; Bhat, Panchami P.; Mehto, Subhash (Frontiers in Immunology, 2025)
Inflammation is closely linked to the development and progression of cancer, as well as the effectiveness of cancer treatment. Inflammation is an immune response triggered when the immune system detects harmful stimuli such as pathogens, damaged cells, or toxic substances through pattern recognition receptors (PRRs). This activates signaling pathways and inflammasomes leading to the release of pro-inflammatory cytokines. In chronic inflammation, immune cells such as T and B lymphocytes, play a significant role in amplifying and sustaining the inflammatory response. The Inflammasomes are protein complexes that respond to microbes and danger signals, triggering an inflammatory response. Key inflammasomes, including NLRP3, AIM2, and NLRC4, regulate the release of proinflammatory cytokines and induce pyroptosis. While inflammasome activation is vital for immune defense, its dysregulation is associated with various diseases, including cancer. The relationship between inflammasomes and cancer is complex and varies depending on the context, with studies showing both promotion and inhibition of tumor growth. This review highlights the connection between microbes and radiation induced inflammatory regulators and cancer, stressing the need for research to understand the mechanisms through which inflammasomes and other inflammatory sensors control cancer.